Learning Model of Arabic in Indonesia: A Study of The Curriculum System at Bahrul Ulum Tambakberas Islamic Boarding School, Jombang and an-Nuqayah, Madura - Dita Wahyuni Aristantia; Muhammad Baharuddin; Nur Mazidah; Putri Amalia; Zaenab Tri Lestari (Edumaspul: Jurnal Pendidikan, 2024)
Arabic is the most core subject in Islamic boarding schools. Likewise at the Bahrul Ulum Islamic Boarding School Tambakberas Jombang and the an-Nuqayah Islamic Boarding School Madura. This study discusses the Arabic curriculum applied by the Bahrul Ulum Islamic Boarding School Tambakberas Jombang and the an-Nuqayah Islamic Boarding School Madura with a focus on the research objectives of Arabic learning, Arabic language learning activities, and Arabic language learning materials taught in the two Islamic Boarding Schools. This study uses a qualitative approach by using the form of a case study. The sources of data in this study were the leaders of Islamic Boarding Schools, Arabic language teachers and administrators of the Bahrul Ulum Tambakberas Islamic Boarding Schools in Jombang and the an-Nuqayah Islamic Boarding Schools, Madura. After discussing and analyzing the data, it can be concluded that the two Islamic boarding schools applied different curricula. The Bahrul Ulum Islamic Boarding School Tambakberas Jombang applies an Arabic curriculum for the Salaf Islamic Boarding School which still prioritizes Arabic as a tool for understanding sources of Islamic studies. Meanwhile, at the an-Nuqayah Islamic Boarding School, the modern Islamic Boarding School's Arabic curriculum combines basic Arabic (as a tool) and practical Arabic as a daily communication tool, which in this case is accommodated by the Daar al-Lughah al-Arabiyah wa al-Fiqh al-Salafi institution. However, the two Islamic Boarding Schools have something in common, namely placing Arabic in their respective Madrasah Diniyah programs.